2011
DOI: 10.1158/1940-6207.capr-11-0340
|View full text |Cite
|
Sign up to set email alerts
|

Possible Role of Visfatin in Hepatoma Progression and the Effects of Branched-Chain Amino Acids on Visfatin-Induced Proliferation in Human Hepatoma Cells

Abstract: Obesity and related metabolic abnormalities, including adipocytokine dysbalance, are risk factors for hepatocellular carcinoma (HCC). Visfatin, an adipocytokine that is highly expressed in visceral fat, is suggested to play a role in the progression of human malignancies. Branched-chain amino acids (BCAA) reduce the incidence of HCC in obese patients with liver cirrhosis and prevent obesity-related liver carcinogenesis in mice. In this study, we investigated the possible role of visfatin on HCC progression and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
51
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(58 citation statements)
references
References 43 publications
5
51
0
2
Order By: Relevance
“…Increased iNampt expression also occurs in malignant lymphomas, including diffuse large B-cell lymphoma, follicular B-cell lymphoma, Hodgkin's lymphoma, and peripheral T-cell lymphoma (Table 1). [37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55] eNampt also increases the growth fraction of the hepatocellular carcinoma HepG2 cell line in vitro, suggesting a role for it in hepatocellular carcinoma. 53 Many of these studies have found interesting aspects of Nampt expression in cancer.…”
Section: Nampt Nad + and Cancermentioning
confidence: 99%
See 2 more Smart Citations
“…Increased iNampt expression also occurs in malignant lymphomas, including diffuse large B-cell lymphoma, follicular B-cell lymphoma, Hodgkin's lymphoma, and peripheral T-cell lymphoma (Table 1). [37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55] eNampt also increases the growth fraction of the hepatocellular carcinoma HepG2 cell line in vitro, suggesting a role for it in hepatocellular carcinoma. 53 Many of these studies have found interesting aspects of Nampt expression in cancer.…”
Section: Nampt Nad + and Cancermentioning
confidence: 99%
“…Plasma eNampt is elevated in a variety of human malignancies, including astrocytomas, myeloma, and male oral squamous cell; gastric, endometrial, hepatocellular, and colorectal carcinomas; and invasive breast cancer. [47][48][49]52,53,[90][91][92][93] Interestingly, plasma eNampt increases with increased astrocytoma grade and has been hypothesized to be a prognostic marker. 52 Similarly, eNampt is elevated at tumor higher stages in male oral squamous cell, hepatocellular, endometrial, and invasive breast carcinomas.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Various agents such as acyclic retinoids, branched-chain amino acids [11,18], antihypertensives such as angiotensin-converting-enzyme inhibitors [19], and Cox-2 inhibitors have been clinically introduced. Chemical stimuli including cytokines and growth factors upregulate the expression of Cox-2, and inflammation induces Cox-2 to mediate increased synthesis of prostaglandin E2 (PGE2) and prostacyclin (PGI2) [13].…”
Section: Discussionmentioning
confidence: 99%
“…Anti-viral treatments, such as interferons and nucleoside analogues, have been commonly used for the management of hepatitis B or C virus infections [8,9], respectively. Subsequently, acyclic retinoids [10], branched-chain amino acids, antihypertensives [11], and cyclooxygenase 2 (Cox-2) inhibitors [12] have been clinically introduced.…”
Section: Introductionmentioning
confidence: 99%